Homotherapy for heteropathy of chronic kidney disease and oligoasthenozoospermia through regulating SIRT1/NF-κB pathway by Shenqi pills - Huang, Shuo; Luo, Qihan; Li, Xinyue; Liu, Yiming; Wei, Jiale; Wang, Sichen; Qiu, Ping; Li, Changyu (Frontiers in Pharmacology, 2025)
BackgroundChronic kidney disease (CKD), defined by a glomerular filtration rate (GFR) below 60 mL/min/1.73 m2 for over 3 months, is a significant global health concern, often progressing to end-stage renal disease (ESRD). Oligoasthenospermia (OA), characterized by reduced sperm count or quality, affects male fertility, contributing to infertility in approximately 15% of couples worldwide. Both conditions share features of yang deficiency, including fatigue, cold intolerance, and weakness. Shenqi Pill (SQP), a Traditional Chinese Medicine (TCM) formula, replenishes kidney yang and demonstrates efficacy in treating yang deficiency-related diseases such as CKD and OA. However, the molecular mechanisms underlying its therapeutic effects remain unclear.MethodsThis study combined ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS), network pharmacology, and machine learning to identify SQP’s active compounds and potential targets. A CKD model was induced in C57BL/6 mice via adenine administration, followed by SQP treatment (0.8 or 1.6 g/kg/day) for 50 days. Renal function, histopathology, and molecular pathways were evaluated. Additionally, in vitro assays were performed to validate SQP’s effects on OA using GC-1spg spermatogonia.Results41 compounds in SQP were identified. Network pharmacology suggested SQP ameliorates CKD and OA by modulating cellular senescence, with SIRT1, RELA, and NFKB1 as key targets. In vivo, SQP improved renal dysfunction, reduced glomerular atrophy, tubular dilation, and collagen deposition, with higher doses demonstrating superior efficacy. RNA-Seq analysis highlighted SQP’s regulation of the SIRT1/NF-κB pathway and cellular senescence. ELISA, β-galactosidase staining, and Western blotting confirmed reduced senescence-associated secretory phenotype (SASP) release and normalization of SIRT1/NF-κB1 activity. In vitro, SQP-containing serum alleviated cellular senescence in GC-1spg spermatogonia by mitigating SIRT1/NF-κB1 disruptions without cytotoxicity.ConclusionSQP demonstrates therapeutic potential for CKD and OA by targeting the SIRT1/NF-κB signaling pathway, providing evidence for its clinical application in treating kidney-yang deficiency-related diseases.